Conductive polyurethane acrylate hydrogel with anisotropic structure and preparation method thereof

The preparation of anisotropic conductive polyurethane acrylate hydrogel with anisotropic structures solved the problem of difficult balance between moisturizing properties and conductive properties of conductive hydrogels, and achieved a combination of high conductivity and long-term moisturizing properties, which is suitable for the production of flexible wearable devices.

CN115746490BActive Publication Date: 2025-04-25SHANGHAI INST OF TECH +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211486330.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-04-25
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The difficulty in balancing existing conductive hydrogels between moisturizing properties and conductive properties has resulted in limited application of flexible wearable sensors.

Method used

Anisotropic structured conductive polyurethane acrylate hydrogel was prepared by ice template method. By unidirectionally grown ice crystals as templates, combined with conductive polymer materials and metal ion aqueous solution, low-temperature polymerization was carried out to form a highly conductive and long-term moisturizing hydrogel.

Benefits of technology

It achieves a balance between the high conductivity and long-term moisturizing properties of conductive hydrogels, improves the tensile performance and biocompatibility of hydrogels, and is suitable for the production of flexible wearable devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003962493360000031
    Figure BDA0003962493360000031
  • Figure BDA0003962493360000041
    Figure BDA0003962493360000041
  • Figure BDA0003962493360000061
    Figure BDA0003962493360000061
Patent Text Reader

Abstract

The present invention relates to a conductive polyurethane acrylate hydrogel with anisotropic structure and a preparation method thereof, and belongs to the field of functional polymer technology. The preparation steps are as follows: firstly, a pure aqueous polyurethane acrylate emulsion is synthesized; then, the emulsion is uniformly mixed with an acrylic monomer, a conductive polymer material, an aqueous ultraviolet light initiator and a metal ion aqueous solution to obtain a pre-freezing mixed solution; then, an ice template method is used to induce the formation of an anisotropic microstructure and ultraviolet light curing treatment is performed; finally, the conductive polyurethane acrylate hydrogel with anisotropic structure is thawed at room temperature to prepare the conductive polyurethane acrylate hydrogel; the conductive polyurethane acrylate hydrogel prepared by the present invention has a higher elongation at break in a parallel direction than a conventional isotropic hydrogel, and its elastic modulus is adapted to human skin, and it has excellent conductive properties, and can be used for human life activity detection, and has good application prospects in the field of flexible wearable electronics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymers, and in particular relates to a conductive polyurethane acrylate hydrogel with an anisotropic structure and a preparation method thereof. Background Art

[0002] In recent years, conductive hydrogels have been widely used in soft machines, electronic skin, health monitoring and other fields. As flexible wearable sensors, they play a key role in personalized medicine, clinical diagnosis and real-time continuous physical monitoring. Compared with conventional wearable detection devices, such as smart bracelets and smart watches, conductive hydrogels can adhere to human skin, solving problems such as low sensitivity, poor biocompatibility, insufficient detection range and poor wearing comfort. Therefore, the use of conductive hydrogels is an important step for flexible wearable sensors to move towards portability, accuracy and comfort.

[0003] As a conductive hydrogel widely used in the field of flexible wearables, although its fragility problem has been greatly improved, its mechanical properties, conductive properties and self-healing properties are all fully dependent on the water content of the hydrogel itself, which puts forward new requirements for the moisturizing properties of the conductive hydrogel. At present, the moisturizing methods of conventional hydrogels are hydrophilic long-chain molecular replacement, elastomer coating and salting out of metal salt aqueous solutions. Among them, hydrophilic long-chain molecular replacement will hinder the overall charge transfer speed of the hydrogel, thereby reducing the conductive properties of the hydrogel and increasing the response time of the flexible sensor; the use of elastomer coating will lose the adhesion to human skin; although the salting out of the metal salt aqueous solution does not affect the overall conductive properties of the hydrogel, the hydration capacity of the metal ions used in the salting out is limited, and the effect is often not good when used alone. Therefore, it is necessary to design a new conductive hydrogel structure to solve the problem of balancing moisturizing properties and conductive properties, which is very challenging.

[0004] Unlike conventional isotropic hydrogels, the elongation at break of anisotropic hydrogels perpendicular to the orientation direction (hereinafter referred to as the vertical direction) is comparable to that of isotropic hydrogels of the same formula, and the elongation at break parallel to the orientation direction (hereinafter referred to as the parallel direction) is about five times that of the vertical direction, which greatly improves the tensile properties of the hydrogel. At present, the ice template method has been widely used to prepare anisotropic structures. The polymer emulsion aggregates under the exclusion of ice crystals. Compared with loose isotropic hydrogels, it has a higher polymer density to reduce the evaporation of water at the interface, which is beneficial to the moisture retention of the hydrogel. However, the reaction of diisocyanates and oligomer polyols to form polyurethane cannot proceed normally in environmental conditions below the freezing point. Therefore, there are few reports on the use of ice templates to prepare anisotropic polyurethane hydrogels. Summary of the invention

[0005] In view of the balance problem between the moisture retention and electrical conductivity of the current conductive hydrogel, the present invention provides a conductive polyurethane acrylate hydrogel with an anisotropic structure and a preparation method thereof.

[0006] The present invention uses unidirectionally grown ice crystals as templates, uses conductive polymer materials and metal ion aqueous solutions as charge transfer paths, and uses pure aqueous polyurethane acrylate emulsion as a main component, performs low-temperature polymerization under free radical conditions initiated by an aqueous ultraviolet light initiator, and obtains a polyurethane acrylate hydrogel with an anisotropic structure and high conductivity.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The present invention firstly provides a conductive polyurethane acrylate hydrogel with an anisotropic structure, which is composed of a solid phase and a liquid phase, wherein the solid phase is polyurethane acrylate with an anisotropic structure and a conductive polymer material, accounting for 25-40% of the total mass; the rest is a liquid phase, which is one or a combination of 0.5-1.5 mol / L concentration of ferric chloride aqueous solution, potassium chloride aqueous solution or sodium chloride aqueous solution.

[0009] The present invention further provides a method for preparing a conductive polyurethane acrylate hydrogel with an anisotropic structure, comprising the following steps:

[0010] 1) using pure water-based nano polyurethane acrylate emulsion, adding acrylic monomer, conductive polymer material, water-based ultraviolet light initiator and metal ion aqueous solution in proportion to prepare a freezing pre-mixed solution;

[0011] 2) placing the pre-freezing mixed liquid in a unilateral low-temperature environment, and performing ultraviolet light curing after the mixed liquid is completely frozen to obtain a mixed liquid gel;

[0012] 3) placing the mixed solution in a low temperature environment for 3 to 7 days, taking it out and thawing it at room temperature to obtain a conductive polyurethane acrylate hydrogel with an anisotropic structure.

[0013] In one embodiment of the present invention, in step 1), further, the pure aqueous nano polyurethane acrylate emulsion is an aqueous polyurethane acrylate emulsion without adding any organic solvent, the emulsion particle size is between 80 and 100 nm, and the particle size dispersion index (PDI) is between 0.09 and 0.12.

[0014] Furthermore, the pure aqueous nano polyurethane acrylate emulsion accounts for 20-35wt% of the conductive polyurethane acrylate hydrogel with an overall anisotropic structure.

[0015] In one embodiment of the present invention, in step 1), the composition and content of the pure aqueous nano polyurethane acrylate emulsion are calculated by weight:

[0016]

[0017] In one embodiment of the present invention, the oligomer polyol is selected from one or more of polyoxypropylene glycol (PPG), polyethylene glycol (PEG), and polybutylene adipate glycol (PBA).

[0018] In one embodiment of the present invention, the polyisocyanate is a diisocyanate, preferably one or more of isophorone diisocyanate (IPDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI) and diphenylmethane diisocyanate (MDI).

[0019] In one embodiment of the present invention, the hydrophilic chain extender is selected from one or both of 2,2-dimethylolpropionic acid (DMPA) and 2,2-dimethylolbutanoic acid (DMBA).

[0020] In one embodiment of the present invention, the acrylic acid ester is one or both of hydroxyethyl methacrylate (HEMA) and hydroxyethyl acrylate (HEA).

[0021] In one embodiment of the present invention, the neutralizing agent is one of sodium hydroxide, ammonia water, and triethylamine (TEA).

[0022] In one embodiment of the present invention, in step 1), the preparation method of the pure aqueous nano polyurethane acrylate emulsion is:

[0023] The oligomer polyol is vacuum dehydrated at a temperature of 105-110° C. for 90-120 minutes; a hydrophilic chain extender is added and vacuum dehydrated for 30-60 minutes; under nitrogen protection, the temperature is lowered to 70-85° C., polyisocyanate is added dropwise for reaction for 60-90 minutes; the temperature is lowered to 50-70° C., acrylate is added dropwise for reaction for 20-30 minutes; the temperature is lowered to 40-60° C., a neutralizer is added dropwise for reaction for 20-30 minutes; the obtained waterborne polyurethane acrylate is added with deionized water and emulsified at a rotation speed of 1500-2000 rpm / min for 20-30 minutes to prepare a pure waterborne nano polyurethane acrylate emulsion with a particle size of 80-100 nm.

[0024] In one embodiment of the present invention, in step 1), the conductive polymer material is a product of a complexation between a polymer monomer and lignin sulfonate, specifically a conductive biomass complex particle, and the polymer monomer is one of PEDOT (polyethylene dioxythiophene), PANI (polyaniline) or PPY (polypyrrole).

[0025] In one embodiment of the present invention, in step 1), the amount of the conductive polymer material added is 4-7 wt % of the conductive polyurethane acrylate hydrogel with anisotropic structure.

[0026] In one embodiment of the present invention, in step 1), the preparation method of the conductive polymer material is:

[0027] At a stirring rate of 700 to 800 rpm, 0.3 to 0.5 g of lignin sulfonate was dissolved in 60 to 100 mL of ethanol solution and treated with ultrasound for 10 to 15 min; then 120 to 200 ml of deionized water was gradually added and the stirring rate was maintained for 2 h; finally, the solution was dialyzed with deionized water for 3 days and dried to obtain lignin sulfonate nanoparticles;

[0028] The lignin sulfonate nanoparticles are configured into a lignin sulfonate solution with a concentration of 0.15-0.2wt%, a conductive polymer monomer is added in a mass ratio of 1.2-1.5 relative to the lignin sulfonate and dissolved in an ethanol solution, and stirred vigorously for 20 minutes; ammonium persulfate (1.3-1.5 times the weight of the conductive polymer monomer) is added to the above solution, and the resulting mixture is stirred in an ice bath (0-4°C) for 12 hours to polymerize the conductive polymer and complex with the lignin sulfonate; finally, the conductive biomass complex particles are obtained by dialyzing and washing the mixture with deionized water.

[0029] In one embodiment of the present invention, in step 1), the aqueous ultraviolet photoinitiator is one of photoinitiators 2959 or 1173.

[0030] In one embodiment of the present invention, in step 1), the raw materials used in the freezing pre-mixed solution are calculated by weight, and their composition and content are as follows:

[0031]

[0032] In one embodiment of the present invention, in step 1), the acrylic monomer is one of acrylic acid or acrylamide, and the added amount is 5-15wt% of the conductive polyurethane acrylate hydrogel with an overall anisotropic structure.

[0033] In one embodiment of the present invention, in step 2), a metal block with a side length greater than the diameter of the beaker is placed at the bottom of the insulation container, and an appropriate amount of liquid nitrogen or anhydrous ethanol cooled by dry ice is poured in to pre-cool the metal block, and the liquid level cannot exceed the top of the metal block; after the pre-cooling is completed, a beaker containing the pre-freezing mixed liquid is placed on the metal block and frozen for 15 to 20 minutes; after it is completely frozen, ultraviolet light curing is performed for 10 to 15 minutes to obtain the mixed liquid gel.

[0034] In one embodiment of the present invention, in step 2), the unilateral low-temperature environment is anhydrous ethanol added with dry ice or liquid nitrogen to ensure a unilateral temperature gradient environment below -80°C and from bottom to top.

[0035] In one embodiment of the present invention, in step 3), the low temperature environment is a refrigerator or freezer at -10 to -20°C (preferably -10 to -15°C).

[0036] The present invention also provides an application of an anisotropically structured conductive polyurethane acrylate hydrogel, wherein the anisotropically structured conductive polyurethane acrylate hydrogel is used to prepare a flexible wearable device.

[0037] The present invention modifies polyurethane into polyurethane acrylate emulsion and combines it with a photoinitiator to perform free radical polymerization in a low temperature environment to break through the use restrictions of polyurethane in the ice template method. It not only fills the research gap of preparing anisotropic polyurethane hydrogel using the ice template method, but also prepares a polyurethane acrylate hydrogel with long-lasting moisturizing and high conductivity.

[0038] Compared with the prior art, the beneficial effects of the present invention are embodied in the following aspects:

[0039] The present invention optimizes the conventional practice of elastomer-coated hydrogel for moisturizing based on the design of hydrogel microstructure. The essence of the elastomer-coated moisturizing mechanism is to reduce the interfacial exchange of liquid phase components by using an elastomer that is denser than hydrogel, so the present invention uses the ice template method to break the elastomer into small pieces, and utilizes the exclusion of ice crystals to aggregate the polymer network to form an ordered anisotropic densified network structure. In addition, the conductive particles in the solid phase and the metal salt ions in the liquid phase respectively bear the charge transfer in their respective phases, so the internal structure of the hydrogel designed in this way breaks through the conductive hydrogel's conductive and moisturizing balance dilemma, and realizes the long-lasting high conductive performance characteristics of the conductive hydrogel.

[0040] Moreover, the present invention starts from the biosafety of the materials, and the main materials have excellent biocompatibility, and the frozen precursor mixture does not add any organic solvents that do not participate in the reaction, which can be applied to flexible wearable devices that are in direct contact with human skin. At the same time, the conductive polyurethane acrylate hydrogel with anisotropic structure prepared by the present invention is prepared by an ice template method without environmental pollution. By using ice crystals grown in a single direction as a template, an anisotropic microstructure of aligned pores is obtained, which can effectively alleviate the external force applied locally. Without reducing the mechanical properties of the overall material, the elongation at break and tensile strength in a specific direction are improved. Its elongation at break in the parallel direction is 1500-2000%, and its elongation at break in the vertical direction is 400-750%; the elastic modulus in the parallel direction is 450-550kPa, and the elastic modulus in the vertical direction is 300-400kPa; the conductivity in the parallel direction is 60-80S / m, and the conductivity in the vertical direction is 40-50S / m; the three-day water retention rate is 85-95%.

[0041] In summary, the anisotropic structural conductive polyurethane acrylate hydrogel prepared in the present invention is one of the key materials for flexible wearable devices due to its excellent conductivity, flexibility and biosafety. It can meet the anisotropic requirements of ergonomics and can be widely used in the production of wearable devices. DETAILED DESCRIPTION

[0042] The oligomer polyols, diisocyanates, hydrophilic chain extenders, neutralizers and other reagents used in the following examples of the present invention were all purchased from the exploration platform, and the UV curing box was produced by Shenzhen Guanghuashi Technology Co., Ltd., model GHSZN.

[0043] The present invention is described in detail below with reference to specific embodiments.

[0044] Example 1

[0045] Provided is a method for preparing a conductive polyurethane acrylate hydrogel with an anisotropic structure, comprising the following steps:

[0046] Step 1: Use pure water-based nano-polyurethane acrylate emulsion, add acrylic monomers, conductive polymer materials, water-based ultraviolet light initiators and metal ion aqueous solutions in proportion to prepare a freezing pre-mixed solution.

[0047] Preparation of pure water-based nano-polyurethane acrylate emulsion

[0048] The raw materials used in the preparation process of the pure water-based nano polyurethane acrylate emulsion are calculated by weight, and their composition and content are as follows:

[0049]

[0050] The polybutylene adipate diol was placed in a 250 ml four-necked flask equipped with a mechanical stirrer, a thermometer, a condenser and a dropping funnel, and vacuum dehydrated for 90 minutes at a temperature of 110° C., and then 2,2-dihydroxymethylpropionic acid was slowly added for vacuum dehydration for 60 minutes; after the temperature dropped to 85° C., isophorone diisocyanate and stannous octoate with a mass fraction of 0.08wt% were added dropwise at a rate of one drop per three seconds, and reacted for 60 minutes under nitrogen protection; after the temperature dropped to 70° C., hydroxyethyl acrylate was added dropwise at a rate of one drop per three seconds for reaction for 30 minutes; after the temperature dropped to 60° C., triethylamine was added dropwise at a rate of one drop per three seconds for reaction for 30 minutes; deionized water was added to the obtained waterborne polyurethane acrylate and emulsified at a speed of 2000rpm / min for 20 minutes to prepare a pure waterborne polyurethane acrylate nano-dispersion with a particle size of 86nm.

[0051] Preparation of conductive polymer materials

[0052] 0.3 g of lignin sulfonate was dissolved in 60 mL of ethanol solution in a four-necked flask and ultrasonically treated for 10 min, then 120 ml of water was gradually added at a stirring rate of 700 rpm and the stirring rate was maintained for 2 h, and finally deionized water was used for dialyzing in a 5 kDa cutoff dialysis tape for 3 days, and dried to obtain lignin sulfonate nanoparticles; 0.2 g of the above particles was prepared into 100 mL of 0.2 wt% lignin sulfonate solution, and placed in a 250 ml four-necked flask equipped with a mechanical stirrer, a thermometer, a condenser, and a dropping funnel; 0.3 g of EDOT was dissolved in anhydrous ethanol solution and slowly added to the above solution, then stirred at 1000 rpm for 20 min, and then 0.45 g of ammonium persulfate was added to the above solution; the resulting mixed solution was stirred in an ice bath (4°C) for 24 hours to polymerize the conductive polymer and complex with the lignin sulfonate; the conductive polymer material was obtained by dialyzing for 3 days with a 5 kDa cutoff dialysis tape and washing the mixture with deionized water.

[0053] Prepare the cryoprecipitate

[0054] The components used in the freezing pre-mixed solution are calculated by weight, and their composition and content are as follows:

[0055]

[0056] Step 2: Preparation of anisotropic conductive polyurethane acrylate gel using ice template method

[0057] Place a 20cm*20cm*5cm copper block at the bottom of the insulated container, and pour in an appropriate amount of anhydrous ethanol cooled by dry ice. Note that the liquid level cannot exceed the top of the copper block. Precool for 15 minutes, and place the beaker containing the pre-freezing mixed solution prepared in step 1 on the metal block. After freezing for 20 minutes, take out the beaker and perform UV curing for 15 minutes to obtain the mixed solution gel.

[0058] Step 3: Low temperature polymerization and thawing

[0059] The frozen gel was placed in a -15°C freezer for 3 days, taken out and thawed at room temperature to obtain a conductive polyurethane acrylate hydrogel with an anisotropic structure.

[0060] Example 2

[0061] Provided is a method for preparing a conductive polyurethane acrylate hydrogel with an anisotropic structure, comprising the following steps:

[0062] Step 1: Use pure water-based nano-polyurethane acrylate emulsion, add acrylic monomers, conductive polymer materials, water-based ultraviolet light initiators and metal ion aqueous solutions in proportion to prepare a freezing pre-mixed solution.

[0063] Preparation of pure water-based nano-polyurethane acrylate emulsion

[0064] The raw materials used in the preparation process of the pure water-based nano polyurethane acrylate emulsion are calculated by weight, and their composition and content are as follows:

[0065]

[0066]

[0067] Polyoxyethylene glycol is placed in a 250ml four-necked flask equipped with a mechanical stirrer, a thermometer, a condenser and a dropping funnel, and vacuum dehydrated for 120 minutes at a temperature of 105°C, and then 2,2-dihydroxymethylbutyric acid is slowly added for vacuum dehydration for 30 minutes; after the temperature drops to 75°C, hexamethylene diisocyanate and stannous octoate with a mass fraction of 0.08wt% are added dropwise at a rate of one drop per three seconds, and reacted for 90 minutes under nitrogen protection; after the temperature drops to 60°C, hydroxyethyl methacrylate is added dropwise at a rate of one drop per three seconds for reaction for 20 minutes; after the temperature drops to 45°C, triethylamine is added dropwise at a rate of one drop per three seconds for reaction for 20 minutes; deionized water is added to the obtained hydrophilic polyurethane acrylate and emulsified at a speed of 1600rpm / min for 30 minutes to prepare a pure aqueous polyurethane acrylate nanodispersion with a particle size of 98nm.

[0068] Preparation of conductive polymer materials

[0069] 0.5 g of lignin sulfonate was dissolved in 100 mL of ethanol solution in a four-necked flask and ultrasonically treated for 10 min, then 200 ml of water was gradually added at a stirring rate of 850 rpm and the stirring rate was maintained for 2 h, and finally deionized water was used for dialyzing in a 5 kDa cutoff dialysis tape for 3 days, and dried to obtain lignin sulfonate nanoparticles; 0.5 g of the above particles was prepared into 150 mL of 0.3 wt% lignin sulfonate solution, and placed in a 250 ml four-necked flask equipped with a mechanical stirrer, a thermometer, a condenser, and a dropping funnel; 0.7 g of aniline was dissolved in anhydrous ethanol solution and slowly added to the above solution, then stirred at 1200 rpm for 20 min, and then 0.75 g of ammonium persulfate was added to the above solution; the resulting mixed solution was stirred in an ice bath (4°C) for 24 hours to polymerize the conductive polymer and composite with the lignin sulfonate; the conductive polymer material was obtained by dialyzing for 3 days with a 5 kDa cutoff dialysis tape and washing the mixture with deionized water.

[0070] Prepare the cryogenic precursor mixture

[0071] The components used in the freezing pre-mixed solution are calculated by weight, and their composition and content are as follows:

[0072]

[0073] Step 2: Preparation of anisotropic conductive polyurethane acrylate gel using ice template method

[0074] Place a 20cm*20cm*5cm copper block at the bottom of the insulated container, and pour in an appropriate amount of anhydrous ethanol cooled by dry ice. Note that the liquid level cannot exceed the top of the copper block. Precool for 15 minutes, and place the beaker containing the pre-freezing mixed solution prepared in step 1 on the metal block. After freezing for 15 minutes, take out the beaker and perform UV curing for 10 minutes to obtain the mixed solution gel.

[0075] Step 3: Place the above frozen gel in a -20°C freezer for 6 days, take it out and thaw it at room temperature to obtain a conductive polyurethane acrylate hydrogel with an anisotropic structure.

[0076] Testing method of conductive polyurethane acrylate hydrogel with anisotropic structure obtained in Example 1 and Example 2

[0077] The elongation at break and elastic modulus of the hydrogel of the present invention are tested with reference to the standard GB / T 1040.1 2018. The sample testing equipment is a universal material testing machine of model SUN500 produced by Cardano AL Camp of Italy. The dumbbell-shaped samples of the hydrogel are tested at room temperature without mass change, and the stretching rate is 100 mm / min. The conductivity of the hydrogel of the present invention is measured using a four-probe method. The sample testing equipment is a four-probe resistance tester of model SB110A produced by Shanghai Qianfeng Electronic Instrument Co., Ltd. The square resistance of the material is measured using the four-probe method, and the four-probe method is used to convert the square resistance of the material into conductivity according to formula (1). The three-day moisture retention rate of the hydrogel of the present invention is obtained by weighing the residual mass of the sample after placing it on a dry plane at room temperature for three days, and calculating it according to formula (2).

[0078]

[0079] Where σ is the conductivity, ρ is the resistivity, R is the square resistance measured by four-probe, and d is the sample thickness.

[0080]

[0081] Where W 存 is the moisture retention rate for three days, W0 is the initial mass, and W1 is the mass after three days of storage.

[0082] The characterization results are shown in Table 1:

[0083] Table 1 Test results of materials obtained in Examples 1 and 2

[0084]

[0085]

[0086] It can be seen that the conductive polyurethane acrylate hydrogel prepared by the present invention has a higher elongation at break in the parallel direction than that of conventional isotropic hydrogel, and its elastic modulus is adapted to human skin. At the same time, it has excellent conductive properties and can be used for human life activity detection. It has good application prospects in the field of flexible wearable electronics.

[0087] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing anisotropically structured conductive polyurethane acrylate hydrogel, characterized in that: The following steps are involved: 1) using pure water-based nano polyurethane acrylate emulsion, adding acrylic monomer, conductive polymer material, water-based ultraviolet light initiator and metal ion aqueous solution in proportion to prepare a freezing pre-mixed solution; 2) placing the pre-freezing mixed liquid in a unilateral low-temperature environment, and performing ultraviolet light curing after the mixed liquid is completely frozen to obtain a mixed liquid gel; 3) placing the mixed solution in a low temperature environment for 3 to 7 days, taking it out and thawing it at room temperature to obtain a conductive polyurethane acrylate hydrogel with an anisotropic structure; In step 1), the conductive polymer material is a complex product of a polymer monomer and lignin sulfonate, and the polymer monomer is one of PEDOT, PANI or PPY; The conductive polymer material is added in an amount of 4 to 7 wt % of the conductive polyurethane acrylate hydrogel with an overall anisotropic structure; In step 2), the unilateral low-temperature environment is anhydrous ethanol added with dry ice or liquid nitrogen to ensure a unilateral temperature gradient environment below -80°C and from bottom to top. In step 3), the low-temperature environment is an environment of -10 to -20°C.

2. The method for preparing a conductive polyurethane acrylate hydrogel with an anisotropic structure according to claim 1, characterized in that: In step 1), the pure aqueous nano polyurethane acrylate emulsion is an aqueous polyurethane acrylate emulsion without any organic solvent added, the emulsion particle size is between 80 and 100 nm, the particle size dispersion coefficient is between 0.09 and 0.12, and the pure aqueous nano polyurethane acrylate emulsion accounts for 20 to 35 wt% of the conductive polyurethane acrylate hydrogel with an overall anisotropic structure.

3. The method for preparing a conductive polyurethane acrylate hydrogel with an anisotropic structure according to claim 1, characterized in that: In step 1), the composition and content of the pure water-based nano polyurethane acrylate emulsion are calculated by weight:

4. The method for preparing a conductive polyurethane acrylate hydrogel with an anisotropic structure according to claim 3, characterized in that: The oligomer polyol is selected from one or more of polyoxypropylene glycol, polyoxyethylene glycol, and polybutylene adipate glycol; The polyisocyanate is selected from one or more of isophorone diisocyanate, toluene diisocyanate, hexamethylene diisocyanate and diphenylmethane diisocyanate; The hydrophilic chain extender is selected from one or both of 2,2-dimethylol propionic acid and 2,2-dimethylol butyric acid; The acrylic acid ester is one or both of hydroxyethyl methacrylate and hydroxyethyl acrylate; The neutralizing agent is one of sodium hydroxide, ammonia water and triethylamine.

5. The method for preparing anisotropically structured conductive polyurethane acrylate hydrogel according to claim 1, characterized in that: In step 1), the raw materials used in the freezing pre-mixed solution are calculated by weight, and their composition and content are as follows: In step 1), the acrylic monomer is acrylic acid, and the added amount is 5-15wt% of the conductive polyurethane acrylate hydrogel with an overall anisotropic structure.

6. A conductive polyurethane acrylate hydrogel with an anisotropic structure, characterized in that: The method according to claim 1 is used to prepare the composite material, wherein the solid phase is polyurethane acrylate and conductive polymer material with anisotropic structure, accounting for 25-40% of the total mass; the rest is liquid phase, which is one or any combination of 0.5-1.5 mol / L concentration of ferric chloride aqueous solution, potassium chloride aqueous solution or sodium chloride aqueous solution.

7. The use of the conductive polyurethane acrylate hydrogel with anisotropic structure as claimed in claim 6, characterized in that: The conductive polyurethane acrylate hydrogel with anisotropic structure is used for preparing flexible wearable devices.

Citation Information

Patent Citations

  • Pure waterborne polyurethane acrylate emulsion and preparation method thereof

    CN109749046A

  • Conductive hydrogel device and preparation method and application thereof

    CN110841080A